Communicating telecom fraud risk in anti-telefraud messages: The effects of metaphorical frames on attitudes - Liu, Mengna; Chen, Jinshi (Frontiers in Psychology, 2023)
Introduction With the frequent occurrences of telecom fraud crimes in China, it is very necessary and urgent to carry out effective anti-telefraud risk communication. In the present study, we investigated the role of metaphorical framing in shaping people’s attitudes toward telecom fraud in anti-telefraud messages through two experiments. Methods Participants (N = 547, Experiment 1; N = 604, Experiment 2) were randomly assigned to war-framing, disease-framing, or issue-framing conditions. They were asked to read anti-telefraud messages where metaphorical frames were realized through multiple metaphorical expressions in Experiment 1 and relatively shorter messages where metaphorical frames were only instantiated through one metaphorical word in Experiment 2. Results The results showed that participants without prior experience with telecom fraud perceived severity as significantly higher in the war-framing condition than in the issue-framing condition. Besides, the framing effects were only detected in Experiment 2 where the short anti-telefraud message with limited metaphorical information was provided. Discussion The study reveals that even one metaphorical word is sufficient to build a framework for thinking about complex concepts, like telecom fraud, and prior experience with a certain risk can serve as a moderator of metaphorical framing on people’s risk perceptions. It is also found that the effectiveness of metaphors may be more salient in the genres of a short length such as anti-telefraud banners. The study can shed light on public legal educators whose job is to use effective ways to communicate telecom fraud risk to citizens.